In vitro adventitious shoot regeneration and acclimatisation of Brassica oleracea subsp. italica cv. Green Marvel - Rafanfar, Seyed Ali; Abdul Aziz, Maheran; Abdul Kadir, Mihdzar; Abdul Rashid, Azmi; Haddadi, Fatemeh (Academic Journals, 2011)
Cotyledonary explants of Brassica oleracea subsp. italica (broccoli) cv. Green Marvel were cultured on Murashige and Skoog (MS) medium containing different combinations of the growth regulators 6- benzylaminopurine (BAP) and α-naphthalene acetic acid (NAA) for shoot regeneration. The optimal medium for inducing shoots contained 3 mgl-1 BAP and 1 mgl-1 NAA, which produced a shoot induction percentage of 53.33% and a mean number of 0.43 shoot per explant. The shoots were subsequently rooted in MS medium that contained 0.2 mgl-1 of indol-3-butyric acid (IBA). Different potting media were assessed during plantlet acclimatization. The highest percentage of plant survival (83.33%) was on the medium that contained sand and soil (1:1), while maximum root length (4.37 cm) and plant height (7.87 cm) were attained in potting medium that consisted peat moss, perlite and vermiculite (3:1:1).